2011
DOI: 10.1007/s11293-011-9269-z
|View full text |Cite
|
Sign up to set email alerts
|

State-Building in Resource-Rich Economies

Abstract: Natural resources, Public finance, H2, 01, E62, 010,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 12 publications
0
30
0
Order By: Relevance
“…Knack (2009) provided initial cross-section evidence, partly consistent with this hypothesis. Jensen (2011) provides further evidence from a panel of 30 hydrocarbon-rich economies, finding that a 1 percent increase in hydrocarbon revenues causes a 1.5 percent decrease in non-resource tax effort, a proxy for fiscal capacity. An earlier panel study by Bornhorst et al (2009), on a similar sample of countries and variables, finds a smaller effect: an additional percentage point of revenue from hydrocarbons reduces revenues from other domestic sources by 0.19 percentage points of GDP.…”
Section: Resource Rents Fiscal Capacity and Political Institutionsmentioning
confidence: 83%
“…Knack (2009) provided initial cross-section evidence, partly consistent with this hypothesis. Jensen (2011) provides further evidence from a panel of 30 hydrocarbon-rich economies, finding that a 1 percent increase in hydrocarbon revenues causes a 1.5 percent decrease in non-resource tax effort, a proxy for fiscal capacity. An earlier panel study by Bornhorst et al (2009), on a similar sample of countries and variables, finds a smaller effect: an additional percentage point of revenue from hydrocarbons reduces revenues from other domestic sources by 0.19 percentage points of GDP.…”
Section: Resource Rents Fiscal Capacity and Political Institutionsmentioning
confidence: 83%
“…In support of this idea, Jensen (2011) finds that a 1 percent increase in the share of natural resource rents in total government income is associated with a 1.4 percent lower share of taxation in GDP. While we do not know of research that convincingly demonstrates this conclusion, it is entirely possible that high foreign aid inflows and abundant natural resources have similar consequences, reducing the incentive to generate taxation from domestic sources.…”
Section: Aid and Resource Dependencementioning
confidence: 97%
“…When Besley and Persson (, ) introduced natural resources in their framework, they too predict that natural resource dependence leads to weaker state capacity. Crivelli and Gupta () found evidence of resource revenues having a negative effect on income taxes, while Jensen () suggested that “resource intensification weakens state‐building by impeding the state's fiscal capacity.”…”
Section: Introductionmentioning
confidence: 99%
“…When Persson (2010, 2011) introduced natural resources in their framework, they too predict that natural resource dependence leads to weaker state capacity. Crivelli and Gupta (2014) found evidence of resource revenues having a negative effect on income taxes, while Jensen (2011) suggested that "resource intensification weakens state-building by impeding the state's fiscal capacity." 2 The approach taken in these papers implicitly assumes that citizens automatically increase compliance in response to greater tax enforcement as a part of the state's investments in capacity.…”
Section: Introductionmentioning
confidence: 99%